2012
DOI: 10.1103/physrevb.85.024504
|View full text |Cite
|
Sign up to set email alerts
|

Local structure of the superconductor K0.8Fe1.6+xSe2

Abstract: The local structure of superconducting single crystals of K 0.8 Fe 1.6+x Se 2 with Tc = 32.6 K was studied by x-ray absorption spectroscopy. Near-edge spectra reveal that the average valence of Fe is 2+. The room temperature structure about the Fe, K and Se sites was examined by iron, selenium and potassium K-edge measurements. The structure about the Se and Fe sites shows a high degree of order in the nearest neighbor Fe-Se bonds. On the other hand, the combined Se and K local structure measurements reveal a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 32 publications
6
20
0
Order By: Relevance
“…Analogues of this deficient ThCr 2 Si 2 -type system are afforded by the A 1-x Fe 2-y Se 2 series (A = K, Rb, Cs; x ≈ 0.2; y ≈ 0.4) and EXAFS measurements of some of these materials reveal comparable behavior to that presented herein. [30,31] This deintercalate synthesized by oxidation with iodine solution has a much higher oxidation state for iron than other iron-based superconductors, where typically the iron valence ranges between extremes of +1.5 and +2.5 and is optimal at +1.88 for LaFeAsO 0.88 F 0.12 for electron-doped materials [1] and +2.2 for the hole-doped case of K 0.4 Ba 0.6 Fe 2 As 2 . [8] While NaFe 1.67 As 2 would appear to lie outside the range of superconductivity, our sample derived from stoichiometric www.zaac.wiley-vch.de NaFeAs, like that of Friederichs et al, [26] does exhibit superconductivity but with a superconducting volume fraction derived from the ZFC susceptibility measurement of only 7 % (Friederichs et al reported a volume fraction of about 20 %).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogues of this deficient ThCr 2 Si 2 -type system are afforded by the A 1-x Fe 2-y Se 2 series (A = K, Rb, Cs; x ≈ 0.2; y ≈ 0.4) and EXAFS measurements of some of these materials reveal comparable behavior to that presented herein. [30,31] This deintercalate synthesized by oxidation with iodine solution has a much higher oxidation state for iron than other iron-based superconductors, where typically the iron valence ranges between extremes of +1.5 and +2.5 and is optimal at +1.88 for LaFeAsO 0.88 F 0.12 for electron-doped materials [1] and +2.2 for the hole-doped case of K 0.4 Ba 0.6 Fe 2 As 2 . [8] While NaFe 1.67 As 2 would appear to lie outside the range of superconductivity, our sample derived from stoichiometric www.zaac.wiley-vch.de NaFeAs, like that of Friederichs et al, [26] does exhibit superconductivity but with a superconducting volume fraction derived from the ZFC susceptibility measurement of only 7 % (Friederichs et al reported a volume fraction of about 20 %).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of order is similar to that reported to occur in the related system K 0.8 Fe 1.6 Se 2 compared with β-FeSe from which it is formally derived via deintercalation of iron and a compensating intercalation of potassium. [30,31] In this latter system the comparison of FeSe and K 0.8 Fe 1.6 Se 2 at the Fe K-edge is strikingly similar to that shown in Figure 5, showing that the introduction of vacancies in the anti-PbO type iron selenide layers leads to a loss of well resolved scattering paths outside the first-coordination shell and this is evident in the EXAFS despite the long-range ordering of vacancies and significantly greater long range structural order in the K 0.8 Fe 1.6 Se 2 system as probed by diffraction methods [17] relative to the semi amorphous nature of the Na 1-x Fe 2-y As 2 system (Figure 1 and reference [26] ). Modeling of the EXAFS for the parent material NaFeAs shows strong features from direct and multiple scattering paths out to 6 Å away from the absorbing site.…”
Section: Extended X-ray Absorption Fine Structure (Exafs)mentioning
confidence: 98%
“…Local structure of AA -Fe2_ ySe2 has been studied by ex tended x-ray absorption fine-structure (EXAFS) measure ments [16][17][18], providing important information on the atomic displacements and nanoscale disorder. Among others, local structure of Ky Fe2_JSe2, studied by polarized EXAFS mea surements, reveals large local disorder with the nanoscale structure being similar to that of a glass [17].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the electrical transport properties and in particular the effects of Cu vacancies on these properties we employ extended X-ray absorption fine structure (EXAFS) spectroscopy, an element-specific atomic-scale probe, at the Cu-K edge to investigate the local surroundings of Cu atoms in both stoichiometric (x¼ 0) and Cu-deficient (x¼0.05) BiCu 1À x OSe samples from room temperature down to 25 K. Previously ZrCuSiAstype superconductive and related iron oxypnictides have been researched by EXAFS, particularly near the superconductivity transition temperature [23][24][25][26], but to our knowledge the present work is the first EXAFS study on the thermoelectric oxychalcogenide compounds. By temperature-dependent measurements, fruitful information like local geometry and lattice dynamics can be deduced.…”
Section: Introductionmentioning
confidence: 99%